ΕΠΙ ΡΩΜΑΙΚΩΙ ΘΑΝΑΤΩΙ dans le décret pour Ménippos de Colophon: «pour la mort d’un Romain» ou «en vue d’un supplice romain»? - Sanchez, Pierre (Chiron. Mitteilungen der Kommission für Alte Geschichte und Epigraphik des Deutschen Archäologischen Instituts, 1970)
This study reviews the fifth ambassadorship to Rome by Menippos of Colophon which allows us to specify the judicial procedure taken before the senate at the request of a Roman citizen against the free city of Colophon and against one of his fellow citizens. The objective is to establish the meaning of the expression: τόν τε κατῃτιαμένον πολίτην ἐπὶ ῾Ῥωμαϊκῶι θανάτωι, «the citizen accused of a Roman death», which has been a subject of controversy for over twenty years. A thorough analysis of the use of the terms θάνατος and Ῥωμαϊκός as well as of the formula ἐπί θανάτῳ shows that this expression did not refer to the indictment held against the citizen of Colophon (Robert, Ferrary, Laffi: «accused of the murder/death of a Roman»), but the punishment which was claimed against him by his Roman accuser (Lehmann: «accused under the pain of death according to Roman custom»). This interpretation is confirmed by the analysis of two episodes reported by Diodoros and Cicero where Roman citizens litigated a cause against Greeks involving the death penalty according to Roman law, stating the intention to make them undergo the supplicium more maiorum.